Analysis of Website Portal Rumah Belajar Using WebQual 4.0 Method and Important Performance Analysis - ADE BAYU SEPTIAN; Eko Darwiyanto; Hetti Hidayati (Indonesia Journal on Computing (Indo-JC), 2021)
Portal Rumah Belajar is implementing E-Government in Presidential Instruction No. 3 of 2003 concerning National Development Policy and Strategy. The government is required to take advantage of advances in information and communication technology by developing e-government-based public services. The Portal Rumah Belajar is a means for students to get various information about the learning material. Therefore this website must be able to present quality information based on user perceptions. Based on previous research that analyzed the Rumah Belajar website, there are deficiencies in usability factors and information quality factors that affect user satisfaction. Therefore, the study discusses the Portal Rumah Belajar Website Analysis topic using the WEBQUAL 4.0 method and Importance Performance Analysis to evaluate the Portal Rumah Belajar website's quality. WEBQUAL 4.0 as a reference for making a questionnaire and Importance Performance Analysis as an analysis in the form of a level of conformity to the gap quantification. The results obtained from the evaluation that the website's quality has a conformity level of 101.16% concluded that the user feels satisfied with the site's service. The gap level has a positive value of 0.04. It can be concluded that users experience satisfaction with the website